(untitled) (Sains Humanika, 2023)
The sun is a great creation of Allah Almighty and a priceless gift for the benefit of mankind. The sun is a major source of energy for the earth’s creatures. Sunlight provides a source of direct radiation, stored radiation, and indirect radiation of energy. Direct radiation energy is the energy that is received directly from the sun. The stored radiation energy is the energy of fossil fuels, biomass, and biogas stored for later use. While indirect radiation energy is wind energy, hydro energy, and ocean thermal energy. These resources have been used from ancient times to the present day and are indispensable to drive the sustainable development of a country. This paper analyzes the information related to the source of energy from the sun and its relationship to the teaching of Islam as contained in the Holy Qu’ran. The resources given to us by God Almighty have no use if we do not use them optimally, efficiently and prudently. The analysis found that the Holy Qu’ran greatly encourages people to make full use of the benefits provided by the energy of the sun. It is hoped that the activities undertaken in utilizing this renewable energy source will not only be fully utilized but will also be used to look for the blessing of Allah Almighty.